A study of $$\varLambda $$ Λ and $$\bar{\varLambda }$$ Λ ¯ polarization splitting by meson field in PICR hydrodynamic model - Yilong Xie; Gang Chen; Laszlo Pal Csernai (European Physical Journal C: Particles and Fields, 2021)
Abstract With the PICR hydrodynamic model, we study the polarization splitting between $$\varLambda $$ Λ and $$\bar{\varLambda }$$ Λ ¯ at RHIC BES energy range, based on the meson field mechanism. Our results fit to the experimental data fairly well. Besides, two unexpected effect emerges: (1) the baryon density gradient has non-trivial and negative contribution to the polarization splitting; (2) for 7.7 GeV Au+Au collisions within the centrality range of 20–50%, the polarization splitting surprisingly increases with the centrality decreases. The second effect might help to explain the significant signal of polarization splitting measured in STAR’s Au+Au 7.7 Gev collisions.